2016
DOI: 10.1177/1090198116668827
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Lifestyle Modification Program Focusing on Physical Activity and Dietary Habits in a Large Group, Community-Based Setting

Abstract: A lifestyle modification program can be successfully implemented in a community setting using a large group format to improve PA and FAV attitudes and behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Recent studies show that educational strategies developed for adults and structured around a theoretical basis are effective in promoting a small to moderate effect on PA (Heath et al, 2012; Sanchez, Bully, Martinez, & Grandes, 2015), healthy dietary habits, and in improving nutritional status (Carlson, Sallis, Ramirez, Patrick, & Norman, 2012; Stoutenberg et al, 2017). However, systematic reviews show that few studies report what theories were used in the interventions (Cervato-Mancuso, Vincha, & Santiago, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that educational strategies developed for adults and structured around a theoretical basis are effective in promoting a small to moderate effect on PA (Heath et al, 2012; Sanchez, Bully, Martinez, & Grandes, 2015), healthy dietary habits, and in improving nutritional status (Carlson, Sallis, Ramirez, Patrick, & Norman, 2012; Stoutenberg et al, 2017). However, systematic reviews show that few studies report what theories were used in the interventions (Cervato-Mancuso, Vincha, & Santiago, 2016).…”
mentioning
confidence: 99%
“…Another study was done aimed at determining whether a PA and nutrition-based lifestyle modification program could be effectively conducted. With 121 participants and a 16-week-long community-based setting, the program improved PA, body weight, as well as PA social support and eating habits’ self-efficacy (Stoutenberg et al, 2017).…”
mentioning
confidence: 99%
“…Several community-based lifestyle modification programs have been effective in large, mixed gender, group settings (Hetherington, Borodzicz, & Shing, 2015;Stoutenberg et al, 2017;West, Elaine Prewitt, Bursac, & Felix, 2008). Within a mixed group setting, there is a greater opportunity for both genders to learn from and positively influence each other to make better health choices (Friedman, Thomas, Owens, & Hebert, 2012;Vimalananda et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The primary focus of the newsletter was to increase self-efficacy for improving dietary habits and increasing physical activity. Self-efficacy plays an important role in both the adoption and maintenance of lifestyle behaviors in adult populations (Stoutenberg et al, 2016). Self-efficacy is the confidence individuals have in their ability to perform a specific behavior such as physical activity and diet.…”
Section: Interventionmentioning
confidence: 99%
“…Self-efficacy is the confidence individuals have in their ability to perform a specific behavior such as physical activity and diet. In both descriptive and experimental studies, self-efficacy has been shown to be a consistent predictor of short- and long-term success in changing health-related behaviors, including physical activity and healthy eating (Hamilton, Warner, & Schwarzer, 2016; Stoutenberg et al, 2016).…”
Section: Interventionmentioning
confidence: 99%